2019
DOI: 10.2147/dhps.s200487
|View full text |Cite
|
Sign up to set email alerts
|

<p>Critical evaluation of the validity of drug promotion materials in Ethiopia</p>

Abstract: Purpose This study was conducted to evaluate the validity of drug promotion materials (DPMs) in Ethiopia. Methods A cross sectional document review was done. DPMs were evaluated for fulfilment of the World Health Organization’s (WHO) criteria for ethical promotion of drugs. They were also evaluated for font size, type of formulation, claims made, pictures depicted, retrievability and source of references used. Results A total of 235 DPMs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, in this study, only 25.2% of screened DPLs had references included, which is less than 48.6% and 42.8% reported in studies conducted in Ethiopia and India. 35,49 An appreciably higher proportion of references was also reported in studies from Saudi Arabia (64%) and Iraq (72%), 34,39 which needs to be a minimum in Nigeria going forward.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in this study, only 25.2% of screened DPLs had references included, which is less than 48.6% and 42.8% reported in studies conducted in Ethiopia and India. 35,49 An appreciably higher proportion of references was also reported in studies from Saudi Arabia (64%) and Iraq (72%), 34,39 which needs to be a minimum in Nigeria going forward.…”
Section: Discussionmentioning
confidence: 96%
“…This is because of the anecdotal belief of the negative effect of these anti-infective medications on the general wellbeing and the need to beef up one's immunity when taking them. Antimicrobials were also the most common medicines promoted in studies conducted in Ethiopia and India 35,44 , while vitamins/nutritional supplements made up 27.9% of all DPLs screened in another Indian study. 45 Cardiovascular (26.4%), endocrine drugs (18.9%), and nutritional supplements (18.9%) were also the most advertised among screened DPLs in a similar study by NAikwadi et al 46 in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, several studies have been conducted to check the compliance of DLP to the criteria mentioned in the guidelines, but the results have been nothing but disappointing. Most studies have found that most of the DPLs analyzed are not entirely compliant with the guidelines [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…(9) The advertisement should mention major interactions with other drugs. (10) The name and address of the manufacturer or distributor should be provided. (11) Reference should be made to scientific literature, as appropriate.…”
Section: Who Criteria For Ethical Promotion Of Drugsmentioning
confidence: 99%